'Pulsed X-ray shadowgraphy of dense, cool, laser-imploded plasma - LUNNEY, JAMES GERARD (American Physical Society, 1978)
Laser implosion of 87-bar neon-filled glass microballoon targets produces a dense, cool plasma whose development in time and space is recorded by pulsed-x-ray shadowgraphy with soft x rays from a separate laser-produced plasma. Compressed densities of 4 g cm-3 are estimated from the data by comparison with numerical simulations of the implosion.
PUBLISHED
Keywords: Physics